Development and update of hospital disaster preparedness and response plan of 25 hub hospitals of Nepal – process documentation - Bajracharya, Sumana; Adhikari, Alisha; Katwal, Srijana; Shrestha, Ashis (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Hospital disaster preparation involves creating systems and processes to enhance a hospital's readiness for emergencies. The first step in crisis management is having a disaster management strategy, mandated by international agreements like the Sendai Framework. The 2015 Nepal earthquake highlighted hospitals' capacity concerns, leading to the inclusion of hub and satellite hospitals in disaster plans. Later, infectious disease management and lessons from COVID-19 were incorporated. The disaster plans for Nepal's 25 hub hospitals, collaborating with Health Emergency Operation Center (HEOC) and Provincial Health Emergency Center (PHEOC), were updated. Workshops aimed to empower participants to own hospital plans. The Hospital Disaster Preparedness and Response Plan (HDPRP) addresses preparedness, response, and recovery, including COVID-19 management. Developed through testing, the HDPRP, along with workshops and engagement strategies, bolsters hospitals' disaster response capabilities.